2021
DOI: 10.1177/00236772211027740
|View full text |Cite
|
Sign up to set email alerts
|

Radiant catalytic ionization improves the microbiological status of rodent facilities without affecting the prooxidative status of mice

Abstract: The main microbial contaminants of rooms in which laboratory rodents are housed are bacteria and fungi. Restriction of microbial growth to below threshold levels requires the application of various sophisticated antimicrobial techniques that must be effective and safe for the animals. Some of the most commonly used techniques, including chemical disinfection, ventilation, filtration, sterilization and radiation, are not always sufficiently effective. The aim of the current study was to evaluate the efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…In the current experiment, after seven days of RCI in a conventional animal room, the number of airborne bacteria decreased by 59% (from 115 to 55 CFU/m 3 ). The results of the microbiological assessment of the air by the sedimentation method were similar to those (63%) obtained by the impact method of air sampling performed under the same experimental conditions [39]. Skowron et al obtained much better sterilization results in laboratory conditions.…”
Section: Microbiological State Of the Environmentsupporting
confidence: 73%
See 1 more Smart Citation
“…In the current experiment, after seven days of RCI in a conventional animal room, the number of airborne bacteria decreased by 59% (from 115 to 55 CFU/m 3 ). The results of the microbiological assessment of the air by the sedimentation method were similar to those (63%) obtained by the impact method of air sampling performed under the same experimental conditions [39]. Skowron et al obtained much better sterilization results in laboratory conditions.…”
Section: Microbiological State Of the Environmentsupporting
confidence: 73%
“…The results of the haematological analyses in our study only confirm the neutral influence of the RCI technology on basic health indicators. Results pertaining to lipid peroxidation in the blood, livers, lungs, and brains of mice exposed to RCI for seven days also indicated the lack of a negative oxidizing effect [39]. However, these results are not a sufficient assessment of the risk that could potentially result from hydrogen peroxide.…”
Section: Haematological Status Of Micementioning
confidence: 95%
“…Thus, the RCI system seems to be an ideal solution ensuring high hygienic standards of animal housing and buildings without hazardous disinfectants. The diminished amount of nitrogen released into the environment is another beneficial aspect of this technology (Niemiec et al 2021). The preliminary studies indicate no harmful effects on animals suggesting the device may be safe for humans, however, further research would be beneficial.…”
Section: Radiant Catalytic Ionization-limitations and Perspectivesmentioning
confidence: 99%
“…The first work on the application of RCI technology in an animal facility and the impact of RCI on mice is very optimistic (Niemiec et al 2021). It showed that the use of RCI reduced the number of micro-organisms and the concentration of ammonia and dust in the air in the experimental room.…”
Section: Radiant Catalytic Ionization-limitations and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation